Comparison of Results of Standard Versus Accelerated Casting Method for Relapsed Club Foot Deformity - Zafar, Muhammad Hassan; Rahman, Obaid Ur; Rafiq, Muhammad Usman; Waleed, Usman; Bukhari, Maira; Razi, Muhammad Hamza (Biological and Clinical Sciences Research Journal, 2025)
Relapsed idiopathic clubfoot remains a significant clinical challenge in pediatric orthopedics, particularly in low-resource countries like Pakistan. While the standard Ponseti method with weekly casting is well-established, the accelerated casting method, requiring more frequent cast changes, offers potential advantages in reducing treatment time without compromising outcomes. Objective: To compare the effectiveness, complication rates, recurrence, and parental satisfaction between standard weekly casting and accelerated bi-weekly casting methods for relapsed clubfoot deformity in a tertiary care hospital in Pakistan. Methods: A prospective comparative study was conducted at the Department of Orthopedics, Benazir Bhutto Hospital, Rawalpindi, from September 15, 2024, to March 15, 2025. A total of 80 children with relapsed idiopathic clubfoot were divided into two equal groups: 40 treated with the standard Ponseti method and 40 with the accelerated method. Outcomes included a number of casts, treatment duration, Pirani score improvement, complication rates, recurrence at 6-month follow-up, and parental satisfaction using a 5-point Likert scale. Data were analyzed using SPSS v25.0, with independent t-tests and chi-square tests applied where appropriate. Results: Both groups achieved comparable deformity correction as reflected by similar final Pirani scores (0.7 ± 0.4 in standard vs. 0.6 ± 0.3 in accelerated, p = 0.312). The accelerated group required significantly fewer casts (5.1 ± 0.9 vs. 6.9 ± 1.1, p < 0.001) and shorter treatment duration (2.6 ± 0.5 weeks vs. 6.9 ± 1.1 weeks, p < 0.001). Complication and recurrence rates were low and statistically similar in both groups. Parental satisfaction was significantly higher in the accelerated group (mean score 4.4 ± 0.5 vs. 3.8 ± 0.7, p = 0.002). Conclusion: The accelerated Ponseti method is a safe and effective alternative to standard casting for relapsed clubfoot, offering faster correction and higher caregiver satisfaction without increasing complications or recurrence. Its adoption may enhance compliance and reduce treatment burden in the Pakistani healthcare setting.